THE ENERGY CONSUMPTION CHALLENGE OF SUSTAINABLE TOURISM - Ambrož, Milan (Journal of Energy Technology, 2024)
This research paper identifies a unique model of culture change to a more sustainable model of energy consumption. Further study suggests strategies to implement cultural changes toward sustainable tourism using cultural traits proposed by researchers of culture change as a vantage point to master the impact of energy consumption on the environment.